Effects of Probiotics on Depressive or Anxiety Variables in Healthy Participants Under Stress Conditions or With a Depressive or Anxiety Diagnosis: A Meta-Analysis of Randomized Controlled Trials - Chao, Limin; Liu, Cui; Sutthawongwadee, Senawin; Li, Yuefei; Lv, Weijie; Chen, Wenqian; Yu, Linzeng; Zhou, Jiahao; Guo, Ao; Li, Zengquan; Guo, Shining (Frontiers in Neurology, 2020)
Background: Probiotics have been associated with the treatment of depression and anxiety. However, the results reported in the literature have been inconsistent, and no meta-analysis specifically reported probiotics used on participants with varying levels of emotional state. Methods: This meta-analysis aimed to study the effectiveness of probiotics on anxious or depressive symptomatology for participants under stress conditions or with a depressive or anxiety disorder diagnosis. Medline, PubMed, EMBASE, and the Cochrane Library were searched through December 2019 for randomized controlled trials (RCTs). The primary outcomes were depression and anxiety scores. Main inclusion criteria: RCTs of probiotics for participants with a mood or emotional disorder diagnosis or under stress situations; and all participants were adults (age ≥ 16 years); Assessed by the modified Jadad assessment scale found seven high-quality studies and three low-quality studies. Results: Ten clinical trials (n= 685 total participants) were included based on the inclusion and exclusion criteria. All studies were assessed as low or moderate risk of bias. The meta-analysis showed that probiotics could significantly reduce the depression scale for patients with anxiety and depression, and healthy participants under stress. However, there was no significant difference between the probiotics and placebo groups in the reduction of patient anxiety scores, even if they are depressive or anxious patients or healthy participants under stress. Subgroup analysis revealed that probiotics had significant effect on depressive symptoms just in patients with depression, and no significant change in anxiety in patients, and no improvement in participant performance under stress. Conclusions: Probiotics could alleviate depressive symptoms in patients with a depression diagnosis or depression scores also in anxiety disorder diagnosis, and suggesting that probiotics may be adjunct therapies for mood or emotional disorders. Therefore, it is essential that probiotics could be more involved in the treatment of patients with depression in the future. The evidence of probiotics successfully treating depression is still insufficient, and more high-quality studies on patients with depression are still needed.